Ta’tsir Istikhdam Istiratijiyyah al-Kharithah al-Zihniyyah al-Taqlidiyyah wa al-Iluktriniyyah ‘ala Isti’ab al-Qawaid al-‘Arabiyyah - Putra, Arifdo; Riyadi, Slamet; Lubis, Arbonas (Universitas Muhammadiyah Sumatera Barat, 2022)
The purpose of this study was to determine the ability of students in grade 2 Islamic boarding school Darul Mukhlisin Karang Baru Aceh Tamiang to understand al-Qawaid an-Nahwiyah before and after learning using conventional and electronic mind-mapping strategies. Then knowing the effect of using conventional and electronic mind mapping on the understanding of al-Qawaid an-Nahwiyah students in grade 2 Darul Mukhlisin Islamic boarding school Karang Baru Aceh Tamiang. The type of research used is field research with experimental quantitative methods. For data processing, the t-test statistical method was used. The results of this study indicate that students' abilities are still weak in understanding al-Qawaid an-Nahwiyah before using conventional and electronic mind-mapping strategies. This can be seen from their average score which only reached 61.7 with a standard deviation of 19.5. After using this strategy, the students' abilities increased and improved, this can be seen from the results of their average score which reached 73.7 with a standard deviation of 16.6. From the data processing using the t-test, the T-count value is 5.364, then the T-count value is greater than T-table because the T-table value is only 2,042. So it can be concluded that there is a significant effect of using conventional and electronic mind mapping in the understanding of students in grade 2 Islamic boarding school Darul Mukhlisin Karang Baru Aceh Tamiang on al-Qawaid an-Nahwiyah.